Evaluation of mechanical properties of ramie/banana reinforced hybrid composites / Sukesh Gupta ... [et al.] - Gupta, Sukesh; Ul Haq, Mir Irfan; Mohan, Sanjay; Anand, Ankush; Raina, Ankush; Dutta, Varun; Vohra, Karan; Kumar, Rajiv (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
In the present article, hybrid polymer composites with ramie and banana fibres have been prepared using hand layup technique. Effect of banana fibre on mechanical properties of ramie/polyester composites has been investigated in the present study. Total five types of hybrid composites were developed based on 0 %, 1 %, 2 %, 3 % and 4 % weight fractions of banana fibres in ramie/polyester composites. A fixed percentage of 20 % by weight was used for ramie fibre in all the developed composites. Ramie fibre was used in bidirectional mat form, while banana fibre in the form of short fibre (10 mm length). Mechanical properties of fabricated composites such as tensile, flexural and impact strength have been evaluated. The results have revealed that hybridization of banana fibre had significant influence on the mechanical properties of ramie/polyester composites. It was observed that hybrid composites with 1 % banana fibre reinforcement exhibited the highest mechanical properties among the developed composites. Increments of 57.9 %, 18.3 % and 9.38 % in tensile, bending and impact strength respectively were observed for hybrid composites with 1 % banana fibre reinforcement in comparison to ramie/polyester composites. The morphological study to examine fractured surface has been carried out by scanning electron microscopy, to evaluate the failure mechanism of composites.